Reprogramming of the microRNA transcriptome mediates resistance to rapamycin - Totary-Jain, H.; Sanoudou, D.; Ben-Dov, I. Z.; Dautriche, C. N.; Guarnieri, P.; Marx, S. O.; Tuschl, T.; Marks, A. R. (J Biol ChemJ Biol ChemJ Biol Chem, 2013)
The mammalian target of rapamycin (mTOR) is a central regulator of cell proliferation that is often deregulated in cancer. Inhibitors of mTOR, including rapamycin and its analogues, are being evaluated as antitumor agents. For their promise to be fulfilled, it is of paramount importance to identify the mechanisms of resistance and develop novel therapies to overcome it. Given the emerging role of microRNAs (miRNAs) in tumorigenesis, we hypothesized that miRNAs could play important roles in the response of tumors to mTOR inhibitors. Long-term rapamycin treatment showed extensive reprogramming of miRNA expression, characterized by up-regulation of miR-17-92 and related clusters and down-regulation of tumor suppressor miRNAs. Inhibition of members of the miR-17-92 clusters or delivery of tumor suppressor miRNAs restored sensitivity to rapamycin. This study identifies miRNAs as new downstream components of the mTOR-signaling pathway, which may determine the response of tumors to mTOR inhibitors. It also identifies potential markers to assess the efficacy of treatment and provides novel therapeutic targets to treat rapamycin-resistant tumors.
Keywords: Animals; Antibiotics, Antineoplastic/*pharmacology; Cell Line, Tumor; Drug Resistance, Neoplasm/*drug effects; Gene Expression Regulation, Neoplastic/*drug effects; Mice; MicroRNAs/*biosynthesis; Neoplasm Proteins/metabolism; RNA, Neoplasm/*biosynthesis; Signal Transduction/drug effects; Sirolimus/*pharmacology; Time Factors; TOR Serine-Threonine Kinases/metabolism; Transcriptome/*drug effects